TINJAUAN YURIDIS PENGEMBALIAN MAHAR SETELAH PERCERAIAN MENURUT KOMPILASI HUKUM ISLAM (Studi Terhadap Putusan Pengadilan Agama Wonosari Nomor : 1023/Pdt.G/2009/PA.Wno) - Icha Rezky; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Pillars in marriage is something that must be met in carrying out the marriage. Pillars of marriages arranged by KHI, to perform a marriage there must be a husband, wife nominee, guardian of marriage, two witnesses, and consent and Kabul. In carrying out the final offer and Kabul, the prospective husband would give a dowry to the bride. Mahar is the right of the wife completely. Decision contested divorce Number: 1032 / Pdt.G / 2009 / PA.Wno judges decided to punish the Plaintiff to restore the entire dowry given to her husband. The purpose of this thesis, namely; First, find out about the refund rules dowry by the wife after divorce by KHI. Second, know the basic consideration of the judges against the return of the dowry by the wife after divorce in the decision on case No. 1032 / Pdt.G / 2009 / PA.Wno.From the research problem there are two main things that can be inferred. First, the rules on the return of the dowry by the wife after divorce by KHI which is contained in Article 35 paragraph (1), the husband that his wife mentalak qobla al dukhul obliged to pay half the dowry has been specified in the marriage contract. There is also Article 149 letter c KHI ie paying off the outstanding dowry in full, and half if qobla al dukhul. Second, the legal basis for the consideration of Judges in deciding the return of dowry entirely in Wonosari Religious Court Number: 1023 / Pdt.G / 2009 / PA.Wno) legally are as follows: Article 76 (1) of Law Number 7 of 1986 concerning Religious Court those relating to Article 22 paragraph (2) of Government Regulation No. 9 of 1975 on the implementation of Law No. 1 of 1974 on Marriage, Article 134 KHI, Article 19 letter f Government Regulation No. 9 of 1975 on the implementation of Law No. 1 of 1974 about Marriage, Article 1 of Law No. 1 of 1974 on Marriage, Article 39 paragraph (2) Marriage Act, Section 119 subsection (2) KHI, KHI Article 149 letter c. Suggestions Author, First, the government must immediately update the rules regarding marriage in Indonesia, particularly regarding dowry. Existing regulations are not in accordance with the times which continues to progress. Second, Judge of law enforcement in Indonesia should be able to provide the fairest verdict against existing case. That the parties understand and not feel aggrieved over the judge's decision.Keywords: Marriage - Divorce - Returns Mahar